Mechanism of roof presplitting in nonpillar coal mining technology and its reasonable parameters in hard roof and longwall top-coal caving face. Issue 2 (March 2023) - Wang, Haosen; Wang, Jiong; He, Manchao; Tian, Xichun; Ma, Zimin; Liu, Peng
This article presents an integrated approach for theoretical analysis and numerical modeling to investigate the mechanism of roof presplitting and its reasonable parameters in the hard roof and longwall top-coal caving face. The test site is located in the city of Jinzhong, Shanxi Province, China. The theoretical analysis results indicated that when the presplitting angle remains constant, the tensile stress at the unpenetrated surface is approximately exponentially distributed with the presplitting height. When the presplitting height remains constant, the variation curve of tensile stress at the unpenetrated surface with the presplitting angle is parabolic. As the presplitting height increases, the presplitting angle required for the tensile stress at the unpenetrated face to exceed the ultimate tensile strength of limestone first increases and then decreases. The ground response of retained entry obtained with numerical modeling confirmed the theoretical analysis results. Meanwhile, numerical modeling results also showed that presplitting height affects the volume of the collapse gangues and the structure of the overlying strata above the retained entry. The presplitting angle is effective in reducing the frictional resistance between the collapse gangue and roof structure of retained entry. Moreover, based on the ground response of the retained entries, the reasonable parameters of the roof presplitting were determined at 17 m and 15°. The field application showed that reasonable roof presplitting parameters could achieve satisfactory effects at pressure relief and retained entry in the longwall top-coal caving panel. Furthermore, the proposed design principle of the roof presplitting technique can be applied to other projects.